2008
DOI: 10.1074/jbc.m709439200
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Natriuretic Peptide-initiated cGMP Pathways Regulate Vasodilator-stimulated Phosphoprotein Phosphorylation and Angiogenesis in Vascular Endothelium

Abstract: cGMP is involved in numerous vascular signaling pathways, and abnormalities in these pathways have been implicated in the pathophysiology of hypertension, atherosclerosis, and diabetes (1, 2). In endothelial cells, cGMP is synthesized by two distinct guanylate cyclase (GC) 5 isoforms, the nitric oxide (NO)-activated soluble GC (sGC) and the atrial natriuretic peptide (ANP)-activated particulate GC (GC-A) (2-4). NO, produced by endothelial NO synthase (eNOS), plays a crucial role in a variety of vascular respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 70 publications
(70 reference statements)
7
54
2
Order By: Relevance
“…To the contrary, inhibition of mGC-mediated cGMP synthesis as reported with exposures to ⅐ NO that inhibit ␤ 2 integrins could be important (18). Cytoskeletal localizations play an important role in functional consequences of protein kinases, and cGMP synthesized by mGC can activate PKG and cause VASP phosphorylation (26,43). Results in this study show that addition of 8-br-cGMP abrogates ⅐ NO-dependent ␤ 2 integrin inhibition via PKG.…”
Section: Discussionmentioning
confidence: 55%
“…To the contrary, inhibition of mGC-mediated cGMP synthesis as reported with exposures to ⅐ NO that inhibit ␤ 2 integrins could be important (18). Cytoskeletal localizations play an important role in functional consequences of protein kinases, and cGMP synthesized by mGC can activate PKG and cause VASP phosphorylation (26,43). Results in this study show that addition of 8-br-cGMP abrogates ⅐ NO-dependent ␤ 2 integrin inhibition via PKG.…”
Section: Discussionmentioning
confidence: 55%
“…Together with published observations in macrovascular ECs (9), these results indicate that NPs can act directly on ECs and potentiate endothelial regeneration. One possible action of endothelial GC-A/cGMP/PKG I signaling is the phosphorylation of VASP, a protein associated with focal adhesion sites and adherens junctions (37). Our experiments with primary cultured MLECs obtained from wild-type and GC-A-deficient mice as well as the experiments in RFPECs showed that BNP, via GC-A/cGMP and PKG I, leads to VASP phosphorylation in microvascular endothelia.…”
Section: Figurementioning
confidence: 69%
“…Our experiments with primary cultured MLECs obtained from wild-type and GC-A-deficient mice as well as the experiments in RFPECs showed that BNP, via GC-A/cGMP and PKG I, leads to VASP phosphorylation in microvascular endothelia. In macrovascular human umbilical vein ECs (HUVECs), this pathway has been shown to be important for reorganization of the actin cytoskeleton and endothelial tube formation (37). Other studies in HUVECs showed that PKG phosphorylates p21-activated kinase 1 (Pak1), thereby stimulating Pak/VASP association, which also seems to be important for endothelial migration (38).…”
Section: Figurementioning
confidence: 99%
“…Phosphorylation of VASP at Ser239 serves as a general marker for PKG-dependent activity. In the cardiovascular system VASP is involved in the remodeling of the actin cytoskeleton and enhancement of angiogenesis (15,16). Phosphorylation of VASP by PKG at Ser239 in VSMCs reduced the binding of VASP to actin and interfered with VSMC invasion and contraction of collagen matrixes (19).…”
Section: Other Targets For Pkgmentioning
confidence: 99%